Bursting Oscillation Mechanisms of a Desktop Medical Shaker with Eccentric Turntables Affected by Dry Friction - Rui Qu; Xin Xia (Shock and Vibration)
The main purpose of this article is to investigate the bursting oscillations of the medical shaking tables resulted from friction in practical application. Using the theoretical method of linear loading, the analytic expression of friction acting on an eccentric turntable is derived in detail. Besides, through numerical simulation, the decisive role of friction in bursting oscillations is verified. On this basis, several practical operation plans are proposed to eliminate harmful vibrations. Last but not least, the effectiveness of theoretical methods is validated through example calculations in cases with special parameters.